2021
DOI: 10.1093/cvr/cvab056
|View full text |Cite
|
Sign up to set email alerts
|

Cezanne is a critical regulator of pathological arterial remodelling by targeting β-catenin signalling

Abstract: Aim Pathological arterial remodelling including neointimal hyperplasia and atherosclerosis is the main underlying cause for occluding arterial diseases. Cezanne is a novel deubiquitinating enzyme, functioning as a NF-кB negative regulator, and plays a key role in renal inflammatory response and kidney injury induced by ischemia. Here we attempted to examine its pathological role in vascular smooth muscle cell (VSMC) pathology and arterial remodelling. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 53 publications
0
15
0
Order By: Relevance
“…As described previously [ 32 , 33 ], cell apoptosis was detected in cultured SMCs with the indicated treatments, as shown in the respective figure legend, using a commercial Terminal deoxynucleotidyl transferase dUTP nick end labeling (TUNEL) Assay Kit (11684795910, Sigma, Dorset, UK), according to the manufacturer’s instructions. Cells were co-stained with DAPI.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…As described previously [ 32 , 33 ], cell apoptosis was detected in cultured SMCs with the indicated treatments, as shown in the respective figure legend, using a commercial Terminal deoxynucleotidyl transferase dUTP nick end labeling (TUNEL) Assay Kit (11684795910, Sigma, Dorset, UK), according to the manufacturer’s instructions. Cells were co-stained with DAPI.…”
Section: Methodsmentioning
confidence: 99%
“…C166 cells, a widely used mouse endothelial cell line, were purchased from ATCC (CRL-2581) and maintained in Dulbecco’s Modified Eagle’s Medium (DMEM) supplemented with 10 % FBS and 1 % penicillin/streptomycin, as per the manufacturer’s instructions. Control scramble esiRNA or Vcam1-specific esiRNA (50 nM, final concentration) were transfected into C166 cells using TransIT-X2 Transfection Reagent (Geneflow Limited, Lichfield, UK), according to the manufacturer’s instructions, and as previously described [ 33 ]. MISSION esiRNA is a heterogeneous mixture of siRNAs that all target the same mRNA sequence, resulting in highly specific and effective gene silencing.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, by inhibiting the proliferation and migration of VSMCs, the number of foam cells generated from smooth muscle cells can be reduced, which is conducive to preventing the occurrence and development of AS atherosclerotic plaques and is beneficial for the treatment of AS [8]. However, it has also been proposed that VSMC proliferation and migration play an important role in maintaining the stability of plaques and are important compensatory mechanisms of plaque injury [9]. Therefore, the advantages and disadvantages of therapeutic inhibition of VSMC proliferation and migration in AS are still very controversial, and more experimental evidence is needed.…”
Section: Introductionmentioning
confidence: 99%
“…β-catenin is a critical regulator of the proliferation and migration of VSMCs for vascular remodeling ( 11 ). A previous study has demonstrated that VRK1 can induce the proliferation and migration of gastric carcinoma cells by targeting β-catenin ( 12 ).…”
Section: Resultsmentioning
confidence: 99%